Is It Appropriate to Use the Nafion Membrane in Electrocatalytic N2 Reduction?. Issue 12 (25th August 2019) - Ren, Yongwen; Yu, Chang; Tan, Xinyi; Han, Xiaotong; Huang, Hongling; Huang, Huawei; Qiu, Jieshan
Abstract: The electrocatalytic N2 reduction reaction (ENRR) to ammonia has attracted much attention due to the mild operating conditions, in which the Nafion membrane is generally adopted to separate the ammonia from the anode products. However, it has been mentioned that the Nafion membrane allows ammonia to pass through and traps the ammonia to some extent, but powerful confirmation experiments and effective solutions are still lacking. Herein, it is experimentally confirmed that the use of the Nafion membrane in the ENRR is inappropriate, based on the results that the ammonia can pass through the membrane, be adsorbed on the membrane, and interact with the membrane. This causes a measurement error and accelerates the membrane degradation process, which is unfavorable for ammonia quantification and the long‐term stability operation of the ENRR in practical application. Also, for the first time, a more accurate method to evaluate the activity of the ENRR electrocatalyst using a salt bridge to replace the Nafion membrane is presented. Abstract : Ammonia can pass through the Nafion membrane, be adsorbed on the membrane, and interact with the membrane, and then the transferred ammonia can be electrooxidized in the anode cell at a higher applied potential. Nafion membrane is needed to be replaced considering measurement error of ammonia quantification and the membrane degradation for poor stability.